Advanced Oxidation Processes (AOPs) for treatment of antibiotics in wastewater: A review - Mahdi, Mahdi H; Mohammed, Thamer J; Al-Najar, Jenan A (IOP conference series. Earth and environmental science, 2021)
Antibiotics are a broad group of drugs that are used in human and veterinary medicine. Antibiotics are slow to be degraded, so they can live for a long time in water, and this leads to the possibility of bioaccumulation in the environment. After metabolism, antibiotics are released into the aquatic environment. These compounds can be removed in many different ways, but after reviewing the treatment by advanced oxidation process (AOPs), it was found that this treatment has the ability to completely remove antibiotics from wastewater. This paper provides an overview of the Advanced Oxidation Processes (AOPs) for treatment of antibiotics in wastewater and has focused on Nonphotochemical processes (Ozonation), Photochemical Processes (such as photo-Fenton), heterogeneous photocatalysis (TiO 2 / UV systems) were reviews. These methods achieved very high removal efficiency of antibiotics from industrial wastewater.